The Influence of Religiusity and Halal Label through Halal Awareness Purchase Decisions - Wisnu Mahendri; Junianto Tjahjo Darsono; Achmad Firdiansjah (Budapest International Research and Critics University, 2020)
This study examines four variables namely religiosity, halal labels, halal awareness and purchasing decisions. The purpose of this study is to analyze and explain the effect of religiosity and halal labels on KFC product purchase decisions by testing halal awareness as intervening. The research respondents were KFC consumers in Jombang which were Muslim. A total of 133 respondents were sampled in this study. The analysis technique is descriptive and linear regression for confirmation on a structural equation model built by the researcher. The quantitative approach was chosen to explain the influence between research variables. Data collection using a questionnaire. The results of this study found that religiosity, halal labels and halal awareness had a positive impact on purchasing decisions for KFC products in Jombang. In previous studies, most religiosity variables and halal labels on purchasing decisions were examined without using intervention variables. This study includes an intervention variable, namely halal awareness to see its effect on purchasing decisions.